2001
DOI: 10.1002/ijc.1277
|View full text |Cite
|
Sign up to set email alerts
|

Induction of histone acetylation in mouse erythroleukemia cells by some organosulfur compounds including allyl isothiocyanate

Abstract: In previous studies we observed that some allyl sulfides can cause increased acetylation of histones and differentiation in DS19 mouse erythroleukemia cells. In the present work we observed increased acetylation of histones with allyl isothiocyanate and butanethiol but not with butyl sulfide or butyl disulfide. Increased acetylation of histones was established by change in electrophoretic mobility, incorporation of [ 3 H]acetate or immunoblotting. Histone deacetylase in nuclei of DS19 cells was inhibited 74% b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 26 publications
(19 reference statements)
1
54
0
Order By: Relevance
“…All of the above indicated that DADS induced differentiation in MGC803 cells. Recently, other studies showed that DADS inhibits proliferation and induces differentiation through increased histone acetylation on rat liver and hepatoma and colon tumors [22,23]. The mechanism induced by DADS in MGC803 cells will be explored in our next study.…”
Section: Discussionmentioning
confidence: 91%
“…All of the above indicated that DADS induced differentiation in MGC803 cells. Recently, other studies showed that DADS inhibits proliferation and induces differentiation through increased histone acetylation on rat liver and hepatoma and colon tumors [22,23]. The mechanism induced by DADS in MGC803 cells will be explored in our next study.…”
Section: Discussionmentioning
confidence: 91%
“…This dual PEITC action was more effective than the pharmacological inhibitors of DNMT and HDACs (80). Allyl isothiocyanate treatment of DS19 mouse erythroleukemia cells increased the acetylation of histones with no effect on HDACs (81).…”
Section: Phenethyl Isothiocyanatementioning
confidence: 85%
“…DADS treatment increased global acetylation of H3 and H4 histones and increased their binding on the promoter of p21 gene. These events correlated with HDAC inhibition, upregulation of p21 and cell cycle arrest (81). Treatment of human colon cancer Caco-2 cells and human breast cancer T47D cells with SAMC induced histone acetylation where HDAC activity was inhibited with allyl butyrate (93).…”
Section: Organosulfur Compoundsmentioning
confidence: 89%
“…Lea et al reported for the first time the increased acetylation of histones H3 and H4 in mouse erythroleukemia DS19 and human leukemia K562 after treatment with DADS and AM (Lea et al, 1999). Then, the same group has confirmed those effects in vivo as histone acetylation was induced in liver and Morris hepatoma 7777 in rats treated with DADS and AM (Lea & Randolph, 2001). Data suggested a direct link between histone hyperacetylation and the antiproliferative activity of some garlic components.…”
Section: Modulation Of Histone Acetylationmentioning
confidence: 94%